2014
DOI: 10.3390/ijms150914921
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Repair Enzyme Apurinic/Apyrimidinic Endonuclease (Apex Nuclease) 2 Has the Potential to Protect against Down-Regulation of Chondrocyte Activity in Osteoarthritis

Abstract: Apurinic/apyrimidinic endonuclease 2 (Apex 2) plays a critical role in DNA repair caused by oxidative damage in a variety of human somatic cells. We speculated that chondrocyte Apex 2 may protect against the catabolic process of articular cartilage in osteoarthritis (OA). Higher levels of Apex 2 expression were histologically observed in severely compared with mildly degenerated OA cartilage from STR/OrtCrlj mice, an experimental model which spontaneously develops OA. The immunopositivity of Apex 2 was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…We observed that APEX2 expression in chondrocytes was induced by OA-related catabolic factors in vitro, and was associated with the degeneration of articular cartilage in an in vivo OA mouse model (Fig. 5) 35) .…”
Section: Dna Damage Repair Enzymes In Articular Cartilagementioning
confidence: 81%
See 2 more Smart Citations
“…We observed that APEX2 expression in chondrocytes was induced by OA-related catabolic factors in vitro, and was associated with the degeneration of articular cartilage in an in vivo OA mouse model (Fig. 5) 35) .…”
Section: Dna Damage Repair Enzymes In Articular Cartilagementioning
confidence: 81%
“…Furthermore, downregulation of APEX2 using small interfering RNA decreased chondrocyte activity in vitro 35) . These findings indicate that APEX2 may prevent the oxidative stress-induced downregulation of chondrocyte activity in OA.…”
Section: Dna Damage Repair Enzymes In Articular Cartilagementioning
confidence: 98%
See 1 more Smart Citation
“…Previously, we observed that the HA-AG/type II collagen self-organized complex consisted of 10-500 µm long (2-50 nm diameter) collagen fibers at pH 6-10. 2,34 HA retains AG molecule in the matrix through specific protein-HA interactions. It is thought that HA forms a scaffold for binding large chondroitin sulfate proteoglycans (AG) in the articular cartilage tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were stained with H&E for histological assessment of the general morphology of the repair tissue, or Safranin O/fast green (SO/FG) and toluidine blue, to indicate glycosaminoglycan content as per standard protocols. 34…”
Section: Implantation Of the Self-organized Scaffolds For Cartilage Rmentioning
confidence: 99%